The Role of Value Coherence in Moderating the Effect of Servant Leadership and Organizational Culture on Workforce Agility through Organizational Commitment - Raja Marwan Indra Saputra; Aris Triyono; Yenny Iskandar; Tomy Fitrio (Journal of Economics and Management, 2026)
This study aims to analyze the role of coherence in moderating the effect of servant leadership and organizational culture on workforce agility through organizational commitment. The study is motivated by the increasing organizational demand for human resources that are adaptive and responsive in facing dynamic environmental changes. A quantitative approach was employed using a survey method involving 143 employees of the Regional-Owned Water Utility (Perumda) Tirta Indra in Indragiri Hulu Regency. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that servant leadership and organizational culture have a positive, significant effect on organizational commitment, which, in turn, positively influences workforce agility. In addition, coherence is shown to moderate the relationships among servant leadership, organizational culture, and organizational commitment. These findings suggest that value alignment and individual understanding within the organization (coherence) are critical factors in enhancing the effectiveness of leadership and organizational culture in fostering commitment and workforce agility. This study contributes theoretically by enriching the development of organizational behavior models through the integration of coherence as a moderating variable. It provides practical implications for Perumda Tirta Indra's management in designing leadership strategies and strengthening organizational culture to improve workforce agility.